Learning from health professionals: a user-centred approach to design a wound monitoring platform - Félix, Beatriz (2023)
Health professionals are able to improve the care quality of chronic wounds by monitoring and reporting the wound status. Resorting to visual representations of wound status enhances comprehension by facilitating knowledge transfer to all stakeholders. However, selecting appropriate healthcare data visualisations is a critical challenge and healthcare platforms must be designed to meet their users' needs and constraints. This article describes the methods used to identify the design requirements and inform the development of a wound monitoring platform through a user-centred approach.